Jira Work Management for business teams : accelerate digital transformation and modernize your organization with Jira Work Management - Funk, John (Packt Publishing, Limited, 2022)
Explore all the fundamental concepts and major applications of Jira Work Management to build and manage your business projects efficiently Key Features Get to grips with Jira Core updates Discover how to use all the new JWM features such as lists, templates, calendars, and forms Learn about administration schemes, automation, and simple administration capabilities Book Description Jira Work Management (JWM) is the newest project management tool from Atlassian, replacing Atlassian's previous product, Jira Core Cloud. While Jira Software focuses on development groups, JWM is specifically targeted toward business teams in your organization, such as human resources, accounting, legal, and marketing, enabling these functional groups to manage and enhance their work, as well as stay connected with their company's developers and other technical groups. This book helps you to explore Jira project templates and work creation and guides you in modifying a board, workflow, and associated schemes. Jira Work Management for Business Teams takes a hands-on approach to JWM implementation and associated processes that will help you get up and running with Jira and make you productive in no time. As you explore the toolset, you'll find out how to create reports, forms, and dashboards. The book also shows you how to manage screens, field layouts, and administer your JWM projects effectively. Finally, you'll get to grips with the basics of creating automation rules and the most popular use cases. By the end of this Jira book, you'll be able to build and manage your own Jira Work Management projects and make basic project-related adjustments to achieve optimal productivity. What you will learn Understand how JWM can help your company to increase productivity Discover how to use templates to create projects quickly and with ease Leverage JWM's newest features, including an in-line editable list, a built-in calendar, a roadmap-style timeline, and an updated board Explore custom fields and see the impact of your project screen arrangement Get to grips with simple administration and how schemes can be used to ease maintenance Find out how Atlassian Marketplace apps can extend your Jira product Discover how to use automation to complete routine and repetitive tasks Who this book is for This book is for product managers and project managers who want to learn how to quickly get started with non-software projects in Jira. End users working as part of functional teams, including human resources, finance, legal, and marketing teams will also benefit greatly from this book. Familiarity with Jira is helpful but not required.